The role of thiol/disulfide homeostasis in the differentiation of transudative and exudative pleural effusion - Abuzaina, Osama; Hezer, Habibe; Karalezli, Aysegul; Abuzaina, Seray; Neselioglu, Salim; Erel, Ozcan; Hasanoglu, H. Canan (Annals of Medical Research, 2022)
Aim: The dynamic thiol/disulfide homeostasis performs a major role in keeping up the oxidant-antioxidant equilibrium. We aimed to find the role of dynamic thiol/disulfide balance in pleural effusion transudate-exudate differentiation. This is considered to be the first research investigating the thiol/disulfide homeostasis in pleural fluid. Materials and Methods: This prospective study was conducted in the Clinic of Chest Diseases of Training and Research Hospital. One hundred adult patients with pleural effusion included. 20-100 cc pleural fluid samples were taken through thoracentesis of the patients. These fluids were categorized as exudate and transudate according to Light’s criteria. Automatic spectrophotometric practice which was defined by Erel & Neselioglu was used to gauge thiol/disulfide homeostasis in pleural fluid. Results: Disulfide, total and native thiol levels were significantly higher in the exudative group than the transudative group (p = 0.001). The ratio of disulfide/native thiol and disulfide/total thiol was higher in the transudative group (p = 0.03). In exudates, native thiol/total thiol proportions were higher (p = 0.03). Conclusion: The increased disulfide levels are indicative of increased oxidative stress in exudative pleural fluid. An abnormal thiol/disulfide state may be a major factor in the pathogenesis. These outcomes may conduce to distinguish exudative fluids without requesting synchronous serum thiol/disulfide level measurement.
Keywords: Pleural effusion; oxidative stress; thiol/disulfide homeostasis